(untitled) (Bangladesh Journal of Botany, 2022)
An in vitro study was conducted to assess the antifungal efficacy and potential antifungal compounds of n-butanol fraction of methanolic stem extract of Chenopodium murale L. against Fusarium oxysporum f. sp. lycopersici. In order to get n-butanolic fraction, the methanolic extract was partitioned using n-hexane, chloroform and ethyl acetate to separate non-polar and low polarity compounds. Finally, n-butanol fraction was separated and its 8 concentrations ranging from 1.562 to 200 mg/ml were assessed for antifungal activity against F. oxysporum f. sp. lycopersici. There was 1 to 100% reduction in biomass of F. oxysporum f. sp. lycopersici due to these concentrations. GC-MS analysis of n-butanol fraction showed 25 compounds in it. Literature survey showed that among the identified compounds, 10 showed antifungal activities against different fungi. These antifungal compounds included 2-heptanol, 1-hexanol, 2-hexanol, 3-hexanol, 1- nonyne, decane, tridecane, palmitic acid, 3-octanone and β-sitosterol, could be responsible for antifungal activity against F. oxysporum f. sp. lycopersici in the present study. Bangladesh J. Bot. 51(4): 663-668, 2022 (December)